Magneto mitochondrial dysfunction mediated cancer cell death using intracellular magnetic nano-transducers. (1st June 2021) - Park, Wooram; Kim, Seok-Jo; Cheresh, Paul; Yun, Jeanho; Lee, Byeongdu; Kamp, David W.; Kim, Dong-Hyun
Abstract : Mitochondria targeting magnetic nano-transducers, converting external magnetic fields into physical stress, were developed to induce mitochondria-mediated cell death signaling for effective cancer treatment. Abstract : Mitochondria are crucial regulators of the intrinsic pathway of cancer cell death. The high sensitivity of cancer cells to mitochondrial dysfunction offers opportunities for emerging targets in cancer therapy. Herein, magnetic nano-transducers, which convert external magnetic fields into physical stress, are designed to induce mitochondrial dysfunction to remotely kill cancer cells. Spindle-shaped iron oxide nanoparticles were synthesized to maximize cellular internalization and magnetic transduction. The magneto-mechanical transduction of nano-transducers in mitochondria enhances cancer cell apoptosis by promoting a mitochondrial quality control mechanism, referred to as mitophagy. In the liver cancer animal model, nano-transducers are infused into the local liver tumor via the hepatic artery. After treatment with a magnetic field, in vivo mitophagy-mediated cancer cell death was also confirmed by mitophagy markers, mitochondrial DNA damage assay, and TUNEL staining of tissues. This study is expected to contribute to the development of nanoparticle-mediated mitochondria-targeting cancer therapy and biological tools, such as magneto-genetics.